2012
DOI: 10.1002/chem.201202831
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Applications of Monofluorinated Cyclopropanes

Abstract: The combination of a fluorine atom and a cyclopropane ring, which both possess unique structural and chemical features, can generate new relevant building blocks for the discovery of efficient fluorinated biologically active agents. In this review, we report the different strategies to access monofluorocyclopropanes and highlight some of their attractive biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 105 publications
0
29
0
Order By: Relevance
“…Based on this strategy, the same authors later reported Johnson−Corey−Chaykovsky fluorocyclopropanation using sulfonium reagent 1a 19a with vinyl sulfones or vinyl sulfonamides to access synthetically challenging monofluorocyclopropanes 29 , which previously have been obtained generally via fluorocarbene and fluorocarbenoid chemistry. 16 The best conditions (Scheme the trans product was 0.9 kcal/mol lower in energy than for the corresponding cis-product.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this strategy, the same authors later reported Johnson−Corey−Chaykovsky fluorocyclopropanation using sulfonium reagent 1a 19a with vinyl sulfones or vinyl sulfonamides to access synthetically challenging monofluorocyclopropanes 29 , which previously have been obtained generally via fluorocarbene and fluorocarbenoid chemistry. 16 The best conditions (Scheme the trans product was 0.9 kcal/mol lower in energy than for the corresponding cis-product.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on this strategy, the Veliks group then reported the Johnson-Corey-Chaykovsky fluorocyclopropanation using sulfonium reagent 1a 19a with vinyl sulfones or vinyl sulfonamides to access synthetically challenging monofluorocyclopropanes, 29 which were previously generally obtained via fluorocarbene and fluorocarbenoid chemistry. 16 The best conditions (Scheme 12), which involved sodium hydride as base and THF as an appropriate solvent, exhibited broad scope of functionalized aryl, heteroaryl, and cyclohexyl vinyl sulfones 63 to give fluorocyclopropanes 64a-f with good yields of the major trans-product.…”
Section: Scheme 11 Fluoromethylene Transfer To Aldehydes and Ketones; Isolated Yields Are Given With Nmr Yields In Parenthesesmentioning
confidence: 99%
“…6,9,38 The first report on the synthesis of gem-difluorocyclopropane was published in 1970 by Sargeant. The efficacy of drugs containing fluorine is found to be high due to enhanced activity, bioavailability and retarded drug metabolism.…”
Section: Synthesis Of Gem-difluorocyclopropanesmentioning
confidence: 99%
“…Fluorinated cyclopropanes have become extraordinary structural motifs which attracted much attention in organic synthesis, drug discovery and agrochemistry over the last years . In particular, highly potent compounds bearing a gem ‐difluorocyclopropyl substituent were disclosed in recent patents, e.g.…”
Section: Introductionmentioning
confidence: 99%